Theoretical Significance of the Development of Musical Culture Based on A Qualitative Approach - Boltaev Bekhruz Khamidovich (Researchparks Publishing, 2026)
This article examines the theoretical significance of developing musical culture based on a qualitative approach by analyzing the professional pedagogical competence of a music teacher, its multifaceted nature, and its close connection with pedagogical creativity. It also explores the role of music in human life, its importance in the socio-cultural environment, and its impact on human consciousness. Furthermore, the article elucidates the intonational nature of music, its ability to reflect the inner world of a person, and its distinctive features compared to other forms of art, while substantiating the communicative, educational, cognitive, and aesthetic functions of musical art.